Flat Aesthetic Mastectomy Closure with the Angel Wing Technique to Address Lateral Adiposity: Technique and Outcome Analysis - E. Klenotic; D. Ochoa; K. Stephenson; C. Croswell; S. Sullivan; A. C. Sherman; R. Henry-Tillman (The Breast Journal)
Introduction. Oncologic mastectomy in the setting of obesity poses challenges in achieving a flat closure that includes the lateral adiposity. The angel wing (AW) technique was developed to address this issue. We aim to demonstrate the safety of AW by evaluating incidence of arm lymphedema (AL) and decreased range of motion (dROM) in patients postmastectomy with and without the AW closure. Methods. We performed a single-center retrospective cohort study at an academic referral center of patients who underwent mastectomy with and without the AW technique from May 2014 to October 2022. Those who received breast reconstruction (immediate or delayed), partial mastectomy, and male patients were excluded. The presence of postoperative AL and dROM was evaluated. Subgroup analysis was performed for patient factors including BMI, extent of axillary surgery, PMRT, and pathologic stage. Results. A total of 390 patients met inclusion criteria. Of those, 173 (44.4%) underwent AW and 217 (55.6%) had non-AW mastectomy. Expectedly, the average BMI was significantly higher in the AW cohort (p<0.0001). The overall rate of AL was 51/390 (13.1%), seen in 27 (15.6%) undergoing AW and 24 (11.1%) non-AW (p value = 0.18). While the rate of dROM within the cohort was 52/390 (13.1%), 27 (15.6%) underwent AW vs. 24 (11.1%) non-AW (p value = 0.22), resulting in no statistical significance between AW and non-AW mastectomy upon subsequent development of AL or dROM. Conclusion. Our study demonstrates the AW technique does not convey an increased risk of overall AL or dROM, even when considering known risk factors such as obesity, PMRT, and extent of axillary surgery. As we strive to provide our patients with improved surgical techniques for oncologic resection, we submit that this technique is a viable and safe option for achieving the goals of cosmesis with oncologic safety.